KAJIAN TEKSTUAL TARI DAMPENG AYOHOK DI DESA KILANGAN KECAMATAN SINGKIL KABUPATEN ACEH SINGKIL - Salisna Oktari; Dillinar Adlin (Universitas Negeri Medan, 2019)
ABSTRACT This study aims to describe how the Textual Study of Dampeng Ayohok Dance in Kilangan Village, Singkil District, Aceh Singkil District. The theoretical foundation in this paper is used as a guideline in data collection consisting of textual studies and Dampeng dance which are used as references in conducting this research. The theory used to discuss this research is the theory of textual study by Y. Sumandiyo Hadi. Textual studies see Dampeng dance from the choreographic analysis side of choreographic analysis consisting of unity, repetition or repetition, transition or displacement and sequence. Structural analysis consisting of patterns and various motions. Symbolic analysis (tagging system).The method used by the author in collecting data is by observation, interviews, literature studies and documentation. Observations carried out such as the form of Dampeng dance, recording the results of interviews and carrying out video and photo documentation. Continued to review each Textual consisting of motion form analysis, Structural Analysis and Symbolic Analysis on Dampeng dance in accordance with the theory used. These data are then analyzed by Qualitative Descriptive Methods. The results of this study in terms of choreographical analysis on Dampeng Ayohok dance are analyzed from the form of motion where Dampeng dance consists of eight forms of opening greetings, clapping, mekhe salam, kisar (rotating), standby, holding dakhilebe (parrying from the front), installing steps and rubbing (closing). Structural analysis consists of patterns of motion and range of motion. The pattern of motion in dance is accompanied by a circle pattern and consists of four different forms of motion. Symbolic analysis consists of marking on motion, setting, floor pattern, and poetry. Keywords: Dampeng, Tekstual dance, Aceh Singkil ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan bagaimana Kajian Tekstual tari dampeng ayohok Di Desa Kilangan Kecamatan Singkil Kabupaten Aceh Singkil. Landasan teoritis dalam skripsi ini dijadikan pedoman dalam pengumpulan data terdiri dari kajian tekstual dan tari dampeng ayohok yang dijadikan acuan dalam melakukan penelelitian ini. Teori yang digunakan untuk membahas penelitian ini yaitu teori tentang kajian tekstual oleh Y. Sumandiyo Hadi. Kajian tekstual melihat tari Dampeng dari sisi analisis koreografis analisis koreografi yang terdiri atas kesatuan atau unity, repetisi atau pengulangan, transisi atau perpindahan dan rangkaian. Analisis struktur yang terdiri dari pola-pola dan ragam gerak. Analisis simbolik (sistem penandaan). Metode yang digunakan penulis dalam mengumpulkan data yaitu dengan cara observasi, wawancara, studi kepustakaan dan dokumentasi. Observasi yang dilakukan seperti bentuk tari dampeng, merekam hasil wawancara dan melakukan dokumentasi video dan foto. Dilanjutkan mengkaji setiap Tekstual yang terdiri atas analisis bentuk gerak, Analisis struktural dan analisis simbolik pada tari dampeng sesuai dengan teori yang digunakan. Data-data ini kemudian dianalisis dengan Metode Deskriptif Kualitatif. Hasil penelitian ini dari sisi analisis koreografis pada tari dampeng ayohok dianalisis dari bentuk gerak dimana tari dampeng ayohok terdiri atas delapan bentuk gerak salam pembuka, bertepuk, mekhe salam, kisar (memutar), siaga, menahan dakhilebe (menangkis dari depan), memasang langkah dan membekhesalam (salam penutup). Analisis struktural terdiri atas pola-pola gerak dan ragam gerak. Pola gerak dalam tari dampeng yaitu pola lingkaran dan terdiri atas empat bentuk ragam gerak. Analisis simbolik terdiri dari penandaan pada gerak, setting, pola lantai, dan syair. Kata kunci : Tari Dampeng, Tekstual, Aceh Singkil